Raspberry Pi user guide - Upton, Eben; Halfacree, Gareth (Chichester, West Sussex, United Kingdom : John Wiley & Sons, 2014)
'Raspberry Pi User Guide, 3rdEdition contains everything you need to know to get up and running with Raspberry Pi. This book is the go-to guide for Noobs who want to dive right in. This updated third edition covers the model B+ Raspberry Pi and its software, additional USB ports, and changes to the GPIO, including new information on Arduino and Minecraft on the Pi. You?ll find clear, step-by-step instruction for everything from software installation and configuration to customizing your Raspberry Pi with capability-expanding add-ons. Learn the basic Linux SysAdmin and flexible programming languages that allow you to make your Pi into whatever you want it to be.' --Amazon.com.
Includes index.
'Updated for Model B+ board'--Cover.
Keywords: Raspberry Pi (Computer).; Microcomputers -- Programming; Computer programming